Living arrangements and social support as predictors of mental health and life satisfaction of older adults - Karmaker, Chhanda; Hossain, Afroza; Bakul, Fariea; Raisa, Sumaia Ali (Dhaka University Journal of Biological Sciences, 2018)
The aim of the present study was to investigate whether living arrangement and social support are significant predictors of mental health and life satisfaction among older adults. Data were collected by using convenience sampling technique from 300 older adults (100 living in old home and 200 living in their own home with spouse or children) of Dhaka and Gazipur districts. The instruments used for collecting data were: (1) Demographic and personal information questionnaire, (2) Bangla version of Social Support Scale, (3) Bangla version of General Health Questionnaire (GHQ-12) and (4) Bangla version of Satisfaction with life scale. The results of the current study indicated that the type of living arrangement has the most influence towards mental health (29.05%) and life satisfaction (30.91%) than social support. Older adults who live in own home have higher life satisfaction (M = 25.86) and less mental health problems (M = 32.55) than those living in old home (M = 17.78) and (M = 39.80). The result also revealed that older people living in old homes have higher social support (M = 51.73) than those who are living with children, spouses or other family relatives (M = 48.02)). Dhaka Univ. J. Biol. Sci. 27(1): 17-25, 2018 (January)